Acute poisonings requiring intensive care in childhood and a hidden threat, suicide attempts: a single-center experience - Oto, Arzu; Kılıç, Serbülent; Sahın, Musa (The European Research Journal, 2023)
Objectives: Very few studies have been conducted to identify the conditions that cause poisoning in pediatric patients needing intensive care, both by age group and toxic agent factor. This study will support the development of strategies for poisoning prevention measures by comparing the data in our region with other data in the world. Methods: This study is a single-centered, retrospective study. The baseline status of acute poisoning was defined in pediatric patients aged one month to 18 years who required intensive care hospitalization between November 2017 and March 2022. Results: There were 148 patient admissions due to acute poisonings (5.2% of all admissions, 69.6% females, median age: 13.6 months). Our study revealed that acute poisoning in children is caused mainly by pharmacological (88.5%), oral intake (97.3%) and at home (85.8%). It was observed that intoxication peaked at two different ages; the first peak was at preschool (33.1%), and the second peak was at adolescence (58.7%). In the univariate analysis, females (odds ratio [OR]=4.1), adolescents (OR=167.6), psychiatric drug users (OR=55.5), and multiple drug intoxications (OR=3.6) were associated with more suicides. Being adolescents and using psychiatric medication contributed significantly to suicide attempts in multivariate analysis (OR=145.3 and OR=37.9). None of our patients died. Conclusions: Preventing both poisoning and suicide attempts is the most critical priority. However, we suggest prevention strategies should be strengthened even if mortality is not observed. Furthermore, our study shows that suicide attempts are very likely to be repeated, especially if an underlying psychiatric illness exists.